2017
DOI: 10.1007/s00134-017-4700-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-associated acute kidney injury in the critically ill: systematic review and Bayesian meta-analysis

Abstract: Meta-analysis of matched cohort studies of iodinated contrast medium exposure does not support a significant incidence of acute kidney injury attributable to iodinated contrast media in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 39 publications
0
34
1
2
Order By: Relevance
“…The concept of CI-AKI arose from observation and assumed causality, and despite a lack of rigorous hypothesis testing, has driven clinical practice for more than five decades. While a randomized controlled trial has not been conducted, there is now substantial evidence suggesting that CM contributes minimally, if at all, to the development of AKI [6,7,9,11,13,[15][16][17]. Despite the existence of such evidence, a pervasive preoccupation with what should be referred to as contrast-associated AKI (CA-AKI) persists in clinical practice, medical texts, and even among clinical researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of CI-AKI arose from observation and assumed causality, and despite a lack of rigorous hypothesis testing, has driven clinical practice for more than five decades. While a randomized controlled trial has not been conducted, there is now substantial evidence suggesting that CM contributes minimally, if at all, to the development of AKI [6,7,9,11,13,[15][16][17]. Despite the existence of such evidence, a pervasive preoccupation with what should be referred to as contrast-associated AKI (CA-AKI) persists in clinical practice, medical texts, and even among clinical researchers.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review revealed that this belief has been driven by a large body of uncontrolled data [15]. Meta-analysis of three propensity-matched controlled studies showed a lack of significant difference in AKI incidence among 560 critically ill patients who were exposed or unexposed to CM [15].…”
Section: Contrast Media and Acute Kidney Injury In The Critically Illmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 291 titles and abstracts retrieved, five potentially relevant reviews were identified. However, the results from three reviews had limited applicability to the outpatient population considered in this assessment, as they were of kidney transplant patients, 84 critically ill patients, 85 and a mixture of emergency, ICU and inpatients. 86 In the two remaining reviews, the quality of included studies was limited because the studies lacked non-contrast agent control groups.…”
Section: Pragmatic Reviews Of Further Evidence To Inform the Economicmentioning
confidence: 99%
“…-У пациентов с наличием факторов риска контрастиндуцированного ОПП (КИ-ОПП) следует проводить профилактику путем инфузии изотонического раствора хлорида или бикарбоната натрия [85,86]. Уровень достоверности (доказательности) A. Уровень убедительности рекомендации I.…”
Section: нефротоксические препараты в периоперационном периодеunclassified